PENGARUH EKSPOR, TABUNGAN BRUTO, DAN PEMBENTUKAN MODAL BRUTO TERHADAP PERTUMBUHAN EKONOMI - Fitria, Eka Afridayani (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2022)
Economic growth in Indonesia can change because it is influenced by several factors. The purpose of this study is to find out how the influence of exports, gross savings, and gross capital formation on economic growth in Indonesia in 1991-2020. The data used for this research is secondary data from the World Bank sources which are time series in 1991-2020. The analytical model used is regression analysis using the Error Correction Model (ECM) method. The tests used in the model are Stationarity Test, Cointegration Test, Classical Assumption Test (Normality, Multicollinearity, Heteroscedasticity, Autocorrelation). The result of this research is that in the long term variable, export and gross capital formation have an effect on economic growth, while gross savings have no effect on economic growth. In the short term, only savings variables affect economic growth, while exports and capital formation variables do not affect economic growth.